2016
DOI: 10.1080/14649357.2016.1215511
|View full text |Cite
|
Sign up to set email alerts
|

Participation, scenarios and pathways in long-term planning for climate change adaptation

Abstract: This article describes a climate change adaptation planning process triggered by a group of researchers and stakeholders in a context where no collective responses or long-term plans for protecting a vulnerable coastal system had been initiated, despite local perceptions of vulnerability and risk. The case study shows the application of two methods: scenario workshops and adaptation pathways in the context of a participatory action research methodological design. Participatory action research and qualitative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…A multi-method approach is important to develop sustainable adaptation plans, which can benefit from using Geographic Information System maps and provide local stakeholders with a clear visual representation of risks (Wood Table 6 Level of knowledge on climate change global and local impacts, and on mitigation and adaptation measures; and knowledge on climate change in comparison with the existence of a specific department/commission for climate change issues. and Stocker, 2009;Campos et al, 2016b). Once potential measures are identified, the planning process could include a prioritization of measures and an assessment of costs and benefits, taking into account future climatic uncertainties and the social and environmental impacts of different measures (Hallegatte, 2009;Haasnoot et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A multi-method approach is important to develop sustainable adaptation plans, which can benefit from using Geographic Information System maps and provide local stakeholders with a clear visual representation of risks (Wood Table 6 Level of knowledge on climate change global and local impacts, and on mitigation and adaptation measures; and knowledge on climate change in comparison with the existence of a specific department/commission for climate change issues. and Stocker, 2009;Campos et al, 2016b). Once potential measures are identified, the planning process could include a prioritization of measures and an assessment of costs and benefits, taking into account future climatic uncertainties and the social and environmental impacts of different measures (Hallegatte, 2009;Haasnoot et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Butler et al (2014Butler et al ( , 2015Butler et al ( , 2016aButler et al ( , 2016c, Butler (2016b), Skewes et al (2016) and Wise et al (2016) are all drawn from a single case of AP planning for livelihoods in Nusa Tenggara Barat Province, Indonesia. Three by Barnett et al (2011Barnett et al ( , 2014aBarnett et al ( , 2014b refer to AP planning for a coastal area in Victoria Australia, and two by Campos et al (2016aCampos et al ( , 2016b relate to a case of AP planning for a coastal area in Portugal. Consequently, these were grouped as three cases, which meant the review found eight cases of participatory AP planning across five policy issues, in eight different locations across four countries.…”
Section: Identified Cases Of Participatory Ap Approachesmentioning
confidence: 99%
“…In the Portuguese case (Campos et al 2016a(Campos et al , 2016b, the research team drafted pathways between two scenario planning workshops. In a subsequent workshop, printed copies of the draft pathways were given to participants who worked in groups to sketch new pathways on top of those drafts.…”
Section: Identifying Actions and Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have developed and applied participatory approaches for climate change adaptation [23][24][25], including for the management of water resources under climate change [26,27]. Quantitative simulation models are frequently used to provide detailed and important insights in the effects of water management under climate change [28][29][30].…”
Section: Introductionmentioning
confidence: 99%